Platelet transfusion in thrombocytopenic horses. (12th March 2013) - Dunkel, B.
Summary Platelet transfusions might be indicated in horses with thrombocytopenia. The need for a transfusion cannot be determined by platelet numbers alone, as primary or co‐existing disease processes, platelet function and age of the recipient also need to be considered. In patients with no co‐morbidities, relevant bleeding is uncommonly observed with platelet counts >10 x 109/l and a therapeutic approach with initiation of treatment when signs of bleeding are observed might be justified.